Radical Socialism, Simplified Serialism: John Weinzweig and CBC Wartime Radio Drama during the Second World War - Sumner, Carolyne (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2016)
Radio drama was a quintessential source of entertainment for Canadian audiences during the Second World War, and the Canadian Broadcasting Corporation (CBC) used the art form to distribute propaganda and garner support for the Canadian war effort. Similarly, radio drama became an essential artistic outlet for artists and composers to articulate their political beliefs to a national audience. This article frames Canadian composer John Weinzweig’s works for the CBC radio drama series New Homes for Old (1941) in light of Canada’s wartime socio-political climate and the rise of the Popular Front movement during the 1930s, and suggests that radio drama provided Weinzweig with a national soapbox for his radical socialist ideals during a time of political upheaval.Drawing upon archival materials from Library and Archives Canada, the CBC Music Library Archives, and Concordia University’s Centre for Broadcasting and Journalism Studies, this article builds upon the biographical work of Udo Kasemets (1960), Elaine Keillor (1994), and Brian Cherney (2011). It establishes Weinzweig’s socialist ties and argues that his political leanings prompted him to simplify his serial language in favour of a simplified modernist aesthetic which appealed to Canada’s conservative wartime audiences. Specifically, this study of Weinzweig’s radio works reveals how the composer desired to make serial compositions accessible and palatable, and shows how he incorporated vernacular idioms such as folk songs and national anthems as foils to the elitist European serial aesthetic. Finally, this article demonstrates how Weinzweig, in incorporating these devices, uses a powerful and pervasive medium to promote his unique compositional style and reveals how his simplified serial aesthetic reflects the cultural, political, and aesthetic ideals of leftist socialism and the Popular Front.